Moderate liver impairment has no influence on daptomycin pharmacokinetics - Dvorchik, Barry (Journal of clinical pharmacology, 2004)
Daptomycin (N-decanoyl-L-tryptophyl-L-asparaginyl-L-aspartyl-L-threonylglycyl-L-ornithyl-L-aspartyl-D-alanyl-L-aspartylglycyl-D-seryl-threo-3-methyl-L-glutamyl-3-anthraniloyl-L-alanine-lactone) is a novel cyclic lipopeptide antibiotic derived from the fermentation of Streptomyces roseosporus. Daptomycin was recently approved for the treatment of complicated skin and skin structure infections caused by aerobic gram-positive bacteria, including those caused by methicillin-resistant and methicillin-susceptible Staphylococcus aureus. This single-dose, parallel-design, matched-controlled study was designed to evaluate the pharmacokinetics of daptomycin in subjects between ages 18 and 80 years with moderately impaired hepatic function (Child-Pugh Class B, n = 10). Subjects were administered a single intravenous dose (6 mg/kg total body weight) over 30 minutes using a syringe pump. A normal volunteer control group matched by weight (+/-25 lb/11 kg), age (+/-10 years), and sex was included in this study for comparison to the hepatic-impaired group. The pharmacokinetic parameters of daptomycin were similar in both groups. Adverse events occurred only in the hepatic-impaired patients and were consistent with the subjects' disease state. In conclusion, subjects with moderate hepatic impairment receiving daptomycin do not require an adjustment in daptomycin dose or dose regimen.